Клініко-діагностичні аспекти порушень репродуктивного здоров’я жінок, які мешкають в йододефіцитних регіонах - Юзвенко, Т. Ю.; Хабрат, Б. В.; Литвак, О. О.; Лисенко, Б. М.; Гирявенко, О. Я. (Clinical Endocrinology and Endocrine Surgery, 2013)
A study of reproductive function at women with various iod deficiency diseases was held. High frequency of gynecological diseases in iodine deficiency disorders and interrelation between functional disorders of reproductive system and a thyroid gland are established. The necessity of a comprehensive study of the endocrine status, ultrasound and joint management of these patients by gynecologists and endocrinologists was shown.